Evaluation of the effects of ischemic preconditioning on the hematological parameters of rats subjected to intestinal ischemia and reperfusion (Clinics, 2015)
OBJECTIVES: Intestinal ischemia/reperfusion often leads to acute lung injury and multiple organ failure. Ischemic preconditioning is protective in nature and reduces tissue injuries in animal and human models. Although hematimetric parameters are widely used as diagnostic tools, there is no report of the influence of intestinal ischemia/reperfusion and ischemic preconditioning on such parameters. We evaluated the hematological changes during ischemia/reperfusion and preconditioning in rats. METHODS: Forty healthy rats were divided into four groups: control, laparotomy, intestinal ischemia/reperfusion and ischemic preconditioning. The intestinal ischemia/reperfusion group received 45 min of superior mesenteric artery occlusion, while the ischemic preconditioning group received 10 min of short ischemia and reperfusion before 45 min of prolonged occlusion. A cell counter was used to analyze blood obtained from rats before and after the surgical procedures and the hematological results were compared among the groups. RESULTS: The results showed significant differences in hematimetric parameters among the groups. The parameters that showed significant differences included lymphocyte, white blood cells and granulocyte counts; hematocrit; mean corpuscular hemoglobin concentration; red cell deviation width; platelet count; mean platelet volume; plateletcrit and platelet distribution width. CONCLUSION: The most remarkable parameters were those related to leukocytes and platelets. Some of the data, including the lymphocyte and granulocytes counts, suggest that ischemic preconditioning attenuates the effect of intestinal ischemia/reperfusion on circulating blood cells. Our work contributes to a better understanding of the hematological responses after intestinal ischemia/reperfusion and IPC, and the present findings may also be used as predictive values.